Pediatric Critical Care Medicine Volume 2: Respiratory, Cardiovascular and Central Nervous Systems - Wheeler, Derek S.; Wong, Hector R.; Shanley, Thomas P. (Springer London : Imprint: Springer, 2014)
The Editors and contributors of this book take seriously the statement that "For all of the science inherent in the specialty of pediatric critical care medicine, there is still art in providing comfort and solace to our patients and their families. No technology will ever replace the compassion in the touch of a hand or the soothing words of a calm and gentle voice."  The four volumes of Pediatric Critical Care Medicine: Basic Science and Clinical Evidence, 2nd Edition detail the continued growth and evolution of the pediatric critical care medicine speciality. They reveal the technological innovations in monitoring and information management and gives witness to the rapid evolution and adoption of novel monitoring techniques, such as continuous venous oximetry and near-infrared spectroscopy. They also cover advances in molecular biology that have led to the era of personalized medicine with the ability to individualize treatment to the unique and specific needs of a patient. As such this volume and its three sister titles will be of immense value to all studying and practicing pediatric critical care medicine or those involved in the management of this group of patients.